THE FUNCTIONAL ROLE OF MORAL AND ETHICAL EDUCATION IN STRENGTHENING PUBLIC SECURITY - Ikromjon Usarov (Periodica Journal, 2026)
This article explores the functional role of moral and spiritual education in strengthening public security. It analyzes the provisions of Uzbekistan’s new Constitution regarding the protection of citizens’ rights and freedoms, as well as the legal foundations of national and public security. The study emphasizes the importance of cooperation between government institutions, civil society actors, and the population. It also underlines the role of legal awareness, the rule of law, and social mobilization in enhancing community safety.
Keywords: Constitution; legal culture; public security; moral education